2022
DOI: 10.18332/tid/153972
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco cessation programs and factors associated with their effectiveness in the Middle East: A systematic review

Abstract: INTRODUCTION In Middle East countries, the average prevalence of tobacco use is relatively high. This systematic review aimed to explore different tobacco cessation programs provided in the Middle East, identify healthcare professionals providing these programs, and the factors associated with their effectiveness. METHODS A systematic review was conducted using an electronic search of PubMed, EMBASE, Cochrane Library, ProQuest, and Web of Science, bibliographic databases between 24 January 2021 and 7 March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…It's important to note that all patients received weekly counseling and monitoring, and while some may have experienced slip-ups, we didn't collect data on the timing of these slip-ups. Non-pharmacological methods such as brief counseling and motivational techniques have been shown to have an impact on smoking cessation, even in the placebo group [ 5 , 23 ]. According to the trial by Wiratmoko et al, some smokers made successful smoking cessation even in the placebo group [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It's important to note that all patients received weekly counseling and monitoring, and while some may have experienced slip-ups, we didn't collect data on the timing of these slip-ups. Non-pharmacological methods such as brief counseling and motivational techniques have been shown to have an impact on smoking cessation, even in the placebo group [ 5 , 23 ]. According to the trial by Wiratmoko et al, some smokers made successful smoking cessation even in the placebo group [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses have shown varying results on the association between smokeless tobacco use and circulatory disease risk, with variations observed across different regions 11 , 35 . For instance, Asian countries have demonstrated an association between smokeless tobacco use and the risk of non-fatal acute coronary events, while European countries have not established a clear and significant association 36 . Limited data exist on smokeless tobacco use and cardiovascular risk in Middle Eastern countries, particularly Saudi Arabia, necessitating further investigation to better understand this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of studies exploring different cessation methods revealed that abstinence rates decreased with time. For example, in one cohort study included in the review, the quit rate was 88.2% at 4 weeks, 54% at 6 months, and only 36% at 12 months after tobacco cessation [18].…”
Section: Introductionmentioning
confidence: 99%